Penerapan Metode Role Model Dalam Pendidikan Agama Islam Untuk Membentukan Karakter Religius - Taufiqur Rohman, Mochamad; nuddin Ridlwan, Burha (ILJ: Islamic Learning Journal, 2025)
This study aims to describe the implementation of the role model method in Islamic religious education and analyse its contribution to the formation of students' religious character at SMPN 1 Jombang. The background to this study is that there are various problems in education, particularly in relation to character. In character building, there needs to be a strategy, one of which is the presence of a role model. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The subjects of this study were Islamic education teachers and eighth-grade students at SMPN 1 Jombang. The results showed that Islamic education teachers at SMPN 1 Jombang consistently applied the role model method through exemplary attitudes, speech, and behaviour in learning activities and outside the classroom. The implementation of this method has proven to be effective in instilling religious values such as honesty, discipline, responsibility, and social awareness in students. Factors supporting the success of the implementation include teacher commitment, school environment support, and active parental involvement. Thus, the role model method plays a significant role in shaping students' religious character in a sustainable manner.